Concentric left ventricular morphology in aerobically trained kayak canoeists - Gates, P. E.; Campbell, I. G.; George, K. P. (Journal of Sports Sciences, 2004)
The aim of the present study was to test the hypothesis that upper body aerobically trained athletes (kayak canoeists) would have greater left ventricular wall thickness, but similar left ventricular diastolic chamber dimensions, compared with recreationally active and sedentary men. Ultrasound echocardiography was used to determine cardiac structure and function in highly trained kayak canoeists (n = 10), moderately active (n = 10) and sedentary men (n = 10). The septal and posterior left ventricular walls were approximately 0.2 cm thicker in kayak canoeists (P < 0.05), and left ventricular mass was 51% and 32% greater (P < 0.05) in canoeists than in the sedentary and moderately trained participants, respectively. There were no differences in left ventricular chamber dimension, suggesting that the kayak canoeists had a concentric pattern of left ventricular adaptation to aerobic upper body training. Scaling the data to body composition indices had no effect on the outcome of the statistical analysis. There were no differences in resting Doppler left ventricular diastolic or systolic function among the groups. Ejection fraction was lower in the kayak canoeists, but the magnitude of the difference was within the normal variability for this measurement. Thus aerobically upper body trained athletes demonstrated a concentric pattern of cardiac enlargement, but resting left ventricle function was not different between athletes, moderately active and sedentary individuals.